Longitudinal study comparing the distribution of phenotypically and genotypically similar antimicrobial resistant Salmonella serovars between pigs and their environment in two distinct swine production systems - Keelara, Shivaramu; Scott, Harvey Morgan; Morrow, William M.; Gebreyes, Wondwossen A.; Correa, Maria; Nayak, Rajesh; Stefanova, Rossina; Thakur, Siddhartha (My University, 2013)
The aim of this longitudinal study was to determine and compare the prevalences and genotypic profiles of antimicrobial-resistant (AR) Salmonella isolates from pigs reared in antimicrobial-free (ABF) and conventional production systems at farm, at slaughter, and in their environment. We collected 2,889 pig fecal and 2,122 environmental (feed, water, soil, lagoon, truck, and floor swabs) samples from 10 conventional and eight ABF longitudinal cohorts at different stages of production (farrowing, nursery, finishing) and slaughter (postevisceration, postchill, and mesenteric lymph nodes [MLN]). In addition, we collected 1,363 carcass swabs and 205 lairage and truck samples at slaughter. A total of 1,090 Salmonella isolates were recovered from the samples; these were isolated with a significantly higher prevalence in conventionally reared pigs (4.0%; n = 66) and their environment (11.7%; n = 156) than in ABF pigs (0.2%; n = 2) and their environment (0.6%; n = 5) (P < 0.001). Salmonella was isolated from all stages at slaughter, including the postchill step, in the two production systems. Salmonella prevalence was significantly higher in MLN extracted from conventional carcasses than those extracted from ABF carcasses (P < 0.001). We identified a total of 24 different serotypes, with Salmonella enterica serovar Typhimurium, Salmonella enterica serovar Anatum, Salmonella enterica serovar Infantis, and Salmonella enterica serovar Derby being predominant. The highest frequencies of antimicrobial resistance (AR) were exhibited to tetracycline (71%), sulfisoxazole (42%), and streptomycin (17%). Multidrug resistance (resistance to ≥3 antimicrobials; MDR) was detected in 27% (n = 254) of the Salmonella isolates from the conventional system. Our study reports a low prevalence of Salmonella in both production systems in pigs on farms, while a higher prevalence was detected among the carcasses at slaughter. The dynamics of Salmonella prevalence in pigs and carcasses were reciprocated in the farm and slaughter environment, clearly indicating an exchange of this pathogen between the pigs and their surroundings. Furthermore, the phenotypic and genotypic fingerprint profile results underscore the potential role played by environmental factors in dissemination of AR Salmonella to pigs.
Longitudinal study of distributions of similar antimicrobial-resistant Salmonella serovars in pigs and their environment in two distinct swine production systems
Keywords: Salmonella; Swine; Antimicrobial resistance; Environment; Slaughter; PFGE